The Quest for the Unprogrammed Human Being - John Schranz (Universidade de Malta – Msida, Malta) (Revista Brasileira de Estudos da Presença, 2014)
Stanislavski tells his actors: The Studio is for Life. Meyerhold adds: Theatre is the art of Man. Craig predicts a new actor: Today he impersonates and interprets; tomorrow he must represent and interpret, and on the third day he will create. Grotowski and Barba harness Oriental theatre’s forces into Performer’s epiphany. At last shedding author dependence to create from himself, the new Performer attains artistic autonomy. Also: unlike other artists he creates by means of himself, with no medium. The role of Director posits an interim stage: without the stable, unifying base of the Author’s text Performer’s hard-earned autonomy could degenerate into ego-centred individualism. Action precedes consciousness, neuroscience tells us. Outside his creative act as artist and in it as materia prima, Performer defies limits. He is subjectobject, a quest for the unprogrammed Human Being.